Athlete monitoring in handball (ATHMON HB): a survey of current practice in professional women`s and men`s handball - Henze, A.-S.; Burger, J.; Matits, L.; Degenhardt, H.; Fehske, K.; Kirsten, J.; Schulz, S. V. W. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Athlete monitoring is becoming increasingly important in elite team sports to optimize performance and prevent injuries and other athletic health problems. A variety of objective and subjective measures are available to monitor external and internal load, well-being, and readiness to train or compete. A comprehensive Athlete Monitoring System (AMS) should include a meaningful combination of these methods and provide analysis and graphical presentation with decision support for coaches. The selection of monitoring methods to establish an AMS is influenced not only by sport-specific considerations, but also by the resources available. Our study aimed to describe the current practice of athlete monitoring in professional handball, and to examine potential gender differences.